1994
DOI: 10.1007/bf02540469
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of all‐trans‐β‐carotene degradation on heating with and without phenylalanine

Abstract: All-trans-f3-carotene was heated in liquid paraffin at 210~ for 15 min in the presence and the absence of phenylalanine to assess the effect of the amino acid on the rate of degradation of all-trans-f3-carotene. The curve that represents all-trans-f3-carotene degradation in both model systems is formed of two distinct parts that correspond, respectively, to the propagation and termination phases of an autocatalytic reaction. The reaction over 1-15 min followed first-order reaction kinetics in both systems, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…But Murphy and others used relatively high levels of antioxidants (0.1% level in the premix) such as tocopherol (with or without ascorbic acid) or BHT/BHA combinations which could retard the degradation of vitamin A palmitate. Also, most previous studies on the degradation of ␤-carotene reported that it fit into first order kinetics (Chou and Breene 1972;Haralampu and Karel 1983;Papadopoulou and Ames 1994;Warthesen 1988, 1990;Ramakrishnan and Francis 1979;Saguy and others 1985;Stefanovich and Karel 1982;Teixeira Neto and others 1981;Walter and Purcell 1974).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…But Murphy and others used relatively high levels of antioxidants (0.1% level in the premix) such as tocopherol (with or without ascorbic acid) or BHT/BHA combinations which could retard the degradation of vitamin A palmitate. Also, most previous studies on the degradation of ␤-carotene reported that it fit into first order kinetics (Chou and Breene 1972;Haralampu and Karel 1983;Papadopoulou and Ames 1994;Warthesen 1988, 1990;Ramakrishnan and Francis 1979;Saguy and others 1985;Stefanovich and Karel 1982;Teixeira Neto and others 1981;Walter and Purcell 1974).…”
Section: Resultsmentioning
confidence: 91%
“…Additionally, amino acids and proteins can complicate vitamin A palmitate degradation in cereals. Some amino acids have antioxidant effects on ␤-carotene degradation, whereas others have pro-oxidant effects (Arya and others 1982;Farag and others 1978;Papadopoulou and Ames 1994;Riisom and others 1980). These amino acids can react with vitamin A degradation products (for example, carbonyl compounds).…”
Section: Resultsmentioning
confidence: 99%
“…The chemical oxidation of carotenoids is generally considered to be an autocatalytic free-radical chain reaction that involves induction, propagation, and termination stages (Goldman and others 1983;Papadopoulou and Ames 1994). The oxidation reactions take place when carotenoids react with singlet oxygen or with freeradical species, such as peroxyl radicals generated during lipid peroxidation (Miller and others 1996).…”
Section: T Is Well Known That Processing Can Be Responsible Formentioning
confidence: 99%
“…In assuming the pseudo-steady-state for the formation rates of the respective radicals in the system similar to the model proposed by Kasaikina et al (12,13), the consumption rate of β-carotene is [11] [ 12] where w i and a in Equation 11 are given as follows: [13] [ 14] where C AOOH is the concentration of hydroperoxide.…”
Section: Construction Of Kinetic Modelmentioning
confidence: 99%
“…This is because most of the oxidation experiments have been performed under special conditions such as high reaction temperatures, short reaction times, and the presence of initiators. The oxidation of β-carotene is generally considered to be an autocatalytic free-radical chain reaction that involves induction, propagation, and termination stages (11). Thus, the consumption curve of β-carotene is mostly sigmoidal.…”
mentioning
confidence: 99%